ANALISIS TINJAUAN YURIDIS TERHADAP PROGRESIFITAS LEGALITAS PERKAWINAN POLIGAMI - Arifin, Mochammad; Slamet (HUNILA : Jurnal Ilmu Hukum dan Integrasi Peradilan, 2023)
Polygamy is not done just for fun, but is done because of a certain cause or problem. From a fiqh perspective, polygamy is a hereditary tradition that has existed since ancient times. However, in this case, polygamy also cannot be carried out haphazardly by people who cannot treat their wives fairly in the future, both in terms of dhohir living and spiritual living and having the limit is only up to 4 wives. As mentioned in Surah An-Nisa Al-Quran (3 and 129). Furthermore, from a positive legal perspective, polygamy is a practice that is not specifically prohibited. However, in this case polygamy must also fulfill the conditions are quite strict, as explained in Article 3 of the Marriage Law Number 1 of 1974, including the conditions for carrying out polygamy, one of which is a wife who is sick or disabled. difficult to bear. treatment and infertility. And finally from the point of view Compilation of Islamic law, the requirements for polygamy are not much different from the requirements of fiqh and UUP. In doing this, the husband must be able to treat his wife fairly and have adequate financial capabilities.